A Comparative Study on the Environmental Awareness and Environmental Attitude among the Undergraduate Students - et. al., Dr. Moyuri Sarma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increase in comprehensive abilities, alertness and sentience towards the biophysical environment and the issues comprising of human interactions and its consequences is known as environmental awareness. Environmental Attitude is the degree of favour or disfavor towards the natural environment. They are latent construct and therefore we cannot observe them directly. The growth of development of awareness, understanding and consciousness towards the biophysical environment and its problems, including human interactions and its effects is known as Environmental Awareness. In other words it means thinking ecologically or in terms of ecological consciousness. The paper aims to study the environmental awareness and environmental attitude among under graduate students and investigates if there is a significant difference between the students of Commerce and Arts streams in terms of their awareness and attitude towards the environment. It is hypothesized that there is no significant difference between the students of Commerce and Arts streams in terms of their awareness and attitude towards the environment. For the purpose of this descriptive study, the investigators have selected a sample of 46 students, (16 in Commerce and 30 in Arts) of the Under-graduate level, from 2 Degree Colleges located within the Guwahati City. Purposive sampling and Simple Random Sampling are used to determine the colleges and the sample respectively. Moreover, the tools used for collecting data are (i) Taj Environmental Attitude Scale by Dr. Haseen Taj and (ii) Environmental Awareness Test by Dr. K. Yeshodhara. t-test has been applied to determine the level of significance of the test results. After analyzing the data, it has been found that there exists a significant difference between the two groups in terms of their awareness towards the environment. However, there is no significant difference between the Commerce and Arts students in terms of their attitude towards the environment